Tai Chi as a Simple Exercise to Increase Immunity and Psychological Well-being: Narrative Review - Nita Fitria; Tati Sumarni; Diana Kusuma Astuti (Universitas Aisyah Pringsewu, 2023)
Background: COVID-19 is a virus that attacks the human respiratory system and is more at risk of attacking someone with a low immunity level. Apart from having a physical impact, COVID-19 also has a psychological impact. Those impacts need efforts to increase immunity and psychological well-being. The effort that we can make is through a sports program. The right kind of exercise is a moderate-intensity exercise that involves thoughts, emotions, and physical sensations, such as yoga, meditation, and Tai Chi. Purpose: This article aims to analyze the effect of Tai Chi on increasing immunity and psychological well-being in the New Normal era. Methods: This article uses the narrative review method with the keyword